2005
DOI: 10.1097/01.ta.0000174732.90517.df
|View full text |Cite
|
Sign up to set email alerts
|

Direct Health Care Costs After Traumatic Spinal Cord Injury

Abstract: Direct costs in the first year after SCI are substantial. In the subsequent 5 years, individuals with SCI will continue to accrue greater costs than the general public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
86
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 15 publications
0
86
1
9
Order By: Relevance
“…Furthermore, and as previously mentioned, Dryden et al 10 found that the initial hospitalization (which included both the initial acute care and inpatient rehabilitation) costs for newly injured SCI patients were approximately $6.3 million (2002 CDN $) or $7.2 million (2005 CDN $), substantially lower than the costs reported in the present study. The present study separated the acute care inpatient index event and the inpatient rehabilitation costs, with the finding that the average total direct costs for rehabilitation are more than three times the average total costs for the acute care inpatient index event, in accordance with the longer length of stay in rehabilitation (mean 90.2 days ± 64.3) 8 versus acute care (mean 21.7 days ± 31.4).…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…Furthermore, and as previously mentioned, Dryden et al 10 found that the initial hospitalization (which included both the initial acute care and inpatient rehabilitation) costs for newly injured SCI patients were approximately $6.3 million (2002 CDN $) or $7.2 million (2005 CDN $), substantially lower than the costs reported in the present study. The present study separated the acute care inpatient index event and the inpatient rehabilitation costs, with the finding that the average total direct costs for rehabilitation are more than three times the average total costs for the acute care inpatient index event, in accordance with the longer length of stay in rehabilitation (mean 90.2 days ± 64.3) 8 versus acute care (mean 21.7 days ± 31.4).…”
Section: Discussioncontrasting
confidence: 52%
“…Further, the data sources do not provide measures of severity such as the American Spinal Injury Association Impairment Scale, neurological outcomes or functional recovery of persons with SCI, which have been previously shown to be substantially associated with direct costs of health care utilization in traumatic SCI. 10,22 Despite these limitations, the current study has several strengths. This study has provided a comprehensive, recent estimate of the direct health care costs of SCI throughout the various stages of medical treatment-the initial acute care episode, inpatient rehabilitation and ED visits and/or hospital readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations